A strategic plan for Lapanday Group of Companies Development Cooperative - Nucum, Gerardo Sebastian R. (Davao City School of Management, University of the Philippines Mindanao, 2006)
The Lapanday Group of Companies Development Cooperative (LGC DC) was founded in August 1987 with the primary purpose of generating funds and extending credit to its members for productive and providential needs. In general, it aims to encourage thrift and savings mobilization among the members for capital formation, and promote the cooperative as a way of life for improving the quality of life of its members. The LGC DC is a closed type cooperative the membership of which is exclusive to Lapanday employees and affiliates only. It is located at Lapanday Agricultural & Development Corporation (LADC) Compound, Mandug, Davao City. The total membership is 1, 520 as of September 30, 2005. It undertakes the following major business activities: credit/kiosk, and trucking/hauling.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, 2006
Keywords: Strategic plan